Eco-friendly foam biocomposites based on cellulose extracted from date palm leaves and low-density polyethylene. (8th December 2020) - Maria, Hanna J; Luyt, Adriaan Stephanus; Popelka, Anton; Nzihou, Ange; Egorov, Vladimir Valentinovich; Krupa, Igor; Al-Ali Al-Maadeed, Mariam A S; Thomas, Sabu
Abstract: The design of composite materials using environmentally compatible materials and adopting sustainable preparation techniques is very necessary for a better environment. The present study is a step towards developing an environmentally friendly alternative to foam-based composites. The aim of the study is to understand the effect of natural fibers from date palms on the property of foam biocomposites. We adopted an environmentally friendly method of compatibilization between the polymer and the fibers for better reinforcement. The compatibility was done by environmentally friendly physical modification using plasma treatment. Plasma treatment provides surface modification and is an economical solution for further processing. In fact, three types of interfaces have been created: (1) by the addition of maleic anhydride, (2) by the use of plasma-treated low-density polyethylene, (3) by the combination of maleic anhydride and plasma. The overall performance was best in the use of plasma treatment alone. The effect was carefully analyzed based on morphological, mechanical and thermal studies. Finally, a morphology–property correlation was established.